2017
DOI: 10.5194/acp-17-6177-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal and source contribution assessments of black carbon over the northern interior of South Africa

Abstract: Abstract. After carbon dioxide (CO 2 ), aerosol black carbon (BC) is considered to be the second most important contributor to global warming. This paper presents equivalent black carbon (eBC) (derived from an optical absorption method) data collected from three sites in the interior of South Africa where continuous measurements were conducted, i.e. Elandsfontein, Welgegund and Marikana, as well elemental carbon (EC) (determined by evolved carbon method) data at five sites where samples were collected once a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
5
28
0
Order By: Relevance
“…The atmospheric lifetime of BC varies from a few days to weeks; therefore, BC undergoes both regional and intercontinental transport (Bond et al, 2013). During transport, its mixing state, morphology and optical properties change (China et al, 2015). As a result, BC has been observed in remote areas such as the polar regions (Huang et al, 2010;Weller et al, 2013;Qi et al, 2017;Xu et al, 2017) and the Tibetan Plateau (Cong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric lifetime of BC varies from a few days to weeks; therefore, BC undergoes both regional and intercontinental transport (Bond et al, 2013). During transport, its mixing state, morphology and optical properties change (China et al, 2015). As a result, BC has been observed in remote areas such as the polar regions (Huang et al, 2010;Weller et al, 2013;Qi et al, 2017;Xu et al, 2017) and the Tibetan Plateau (Cong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The regional impacts of household combustion from towns and cities within a 50 to 100 km radius will influence the air masses measured at Welgegund. A recent study indicated the regional impact of household combustion on black carbon in the north-eastern interior of South Africa [47], while the influence of household combustion on PM10 measured in the industrialised Western Bushveld Igneous Complex that is also one of the major source regions impacting Welgegund was also revealed [48]. The ƩNRRFs of two specific nitrile compounds, i.e.,2,4-pentanedinitrile and cyanogen, which were also detected in other samples that were collected throughout the sampling period, were significantly higher in the PM1 size fraction in the sample collected on 10 May 2011.…”
Section: Nitriles Amides and Ureamentioning
confidence: 99%
“…In contrast, it was higher than measured values in Santa Cruz de Tenerife (Spain), Crete (Greece) and Finland. Chiloane et al, (2017) recorded BC mean concentrations ranging between 0.7 and 1.4 µgm -3 in background sites and sites influenced by industrial activities and/or nearby settlements in South Africa.…”
Section: Black Carbon Variabilitymentioning
confidence: 99%